Collect, Preserve, Access: Applying the Governing Principles of the National Archives UK Government Web Archive to Social Media Content. Issue 1 (1st August 2014) - Espley, Suzy; Carpentier, Florent; Pop, Radu; Medjkoune, Leïla
Abstract : It is The National Archives' responsibility to collect and secure the future of the public record in all its forms and to make it as accessible as possible. The UK Government Web Archive1 (UKGWA) effectively preserves the open digital record. This article will explore the challenges encountered, and the Application Programming Interface (API) based solutions developed, by The National Archives and the Internet Memory Foundation (IMF) in the completion of a pilot project to capture the record as it is published on the social media services Twitter and YouTube. An outline of the wider web archiving programme and its role within the management of the government web estate is provided. The legislative framework that guides web archiving at The National Archives is described as it has necessarily influenced the policy decisions that shaped the solutions developed. A brief overview of some comparative approaches taken by other organizations and commercial services to capturing Twitter content is also presented as context to the policy and technical solutions arrived at by the authors. The National Archives has sought to develop the building blocks of a collection whose growth can be sustained over time. The publication of this part of the archive will be followed by further evaluation and improvements to the initial approach taken.